AFRID Project: Physical and recreational activities for seniors - Costa, Geni de Araújo (Guará Journal, 2025)
AFRID is an outreach project conceived and implemented by both interns and professors of the Physical Education Program at UFU – Federal University of Uberlândia. Since 1989, this project has served the elderly population, providing various forms of recreational physical activity, as well as informative lectures and studies aimed at improving the quality of life and physical, social, and emotional well-being of this age group. The project serves approximately 850 elderly individuals weekly: 650 on the Physical Education campus and 200 in Long-Term Care Facilities for the Elderly (LTCFs) in Uberlândia. Activities developed on the Physical Education Campus include water aerobics, swimming, stretching, gymnastics, strength training, modern and belly dancing, digital inclusion, singing and choir, fitness, and more. Adapted physical activities, artistic activities, and recreational activities are offered at the LTCFs. To foster greater interaction and engagement, social activities are held, such as June and Christmas parties, tourist trips, and the "Aulão," an activity held with the participation of all students and interns. In addition to these gatherings, Senior Citizens’ Week is another annual event held by AFRID, which sees the participation of over 1,000 seniors in each daily activity. Senior Citizens’ Week aims to discuss, analyze, and reflect on issues surrounding the aging process. AFRID has achieved its stated objectives, improving the quality of life and physical, social, and emotional well-being of Uberlândia’s elderly population.